Answer:
d = (sn - 3)/9
Step-by-step explanation:
Answer:
<h2>
</h2>
Step-by-step explanation:
<h3>to understand this</h3><h3>you need to know about:</h3>
<h3>tips and formulas:</h3>
order of PEMDAS
- parentheses
- exponent
- multiplication or
- division
- addition or
- substraction
<h3>let's solve:</h3>
simplify multiplication:
use to simplify:
as we know x¹=x
therefore our final answer is
- <em><u>6</u></em><em><u>5</u></em>
10⁹ + 10⁸ + 10⁷ = 10⁷ (10² + 10¹ + 10⁰)
… = 10⁷ (100 + 10 + 1)
… = 10⁷ × 111
… = (2 × 5)⁷ × 111
… = 2⁷ × 5⁷ × 111
… = 2⁷ × 5⁶ × 555
Hello there! I can help you! So, we would shift two units to the right, which means that we would subtract, and we go down 7 units, which would also make us subtract. For the original equation of y = x - 3, the line would only go down 3 units. The line of the original equation does not go left or right, because there are no absolute value signs between it. With the equation translation of 7 units, you would go down anouther 7 units, and 7 + 3 is 10. So the equation of the new line is y = |x - 2| - 10.
The original equation is where the line infinitely when up and down on a slanted line. In other words, it has no vertex. In the new equation, however, the graph has a vertex, and the lines go up from there. Both graphs have the same slope, except that for the left side of the new equation, the slope is -1, because the line goes down.